The effect of intermittent hypoxic exposure plus sea level swimming training on anaerobic swimming performance - Miller, A.; George, K. (Journal of Swimming Research, 2012)
An approach which has been proposed as a time efficient variant of the "livehigh trainlow" altitude training strategyis that of intermittent hypoxic exposure. The aim of the study was to determine whether 3 weeks of intermittent hypoxic exposure would enhance sea level anaerobic swimming performance. Eight participants (age = 20 +2 years; height =1.77 +4.80m; mass = 72.0 +3.0 kg) took part in the study and were split into two groups: experimental (EXP) and control (CON). For 3 days a week over a 3 week consecutive period, both groups rested for a total of 90 minutes per day in the hypoxic chamber, whilst undergoing their usual training programme. The experimental group rested in a hypoxic chamber at a simulated altitude of 2300m, whilst the control group rested in a hypoxic chamber at sea level conditions. All participants underwent a total of 3 performance tests (100m sprint) 1 week prior to the hypoxic exposure, 2 days post exposure (Post 1) and 9 days post exposure (Post 2). A blood lactate sample was taken at rest, immediately after, 3 and 7minutes after each time trial. Using a two-?way repeated measures ANOVA, the results revealed that there was no significant difference in time for 100m performance (p = 0.431), stroke count (p = 0.824) or stroke rate (p=0.278), but there was a significant increase over time for blood lactate (p < 0.01). This dose of intermittent hypoxic exposure was not sufficient to elicit significant improvements in 100m sprint time in these eight competitive swimmers.